Pemanfaatan Informasi Akuntansi pada Dinas Kesehatan Kota Sibolga untuk Meningkatkan Kualitas Pengambilan Keputusan - Orita Renta; Rini Indahwati; Yulifati Laoli (Mahesa Research Center, 2024)
This study aims to analyze the utilization of accounting information in decision-making at the Health Department of Sibolga City, particularly examining the quality of accounting information and its impact on budget planning and performance evaluation. The study uses two main variables: the quality of accounting information, measured by relevance, reliability, timeliness, and completeness, and decision-making, focused on budget planning and performance evaluation. This research employs a descriptive qualitative approach through a case study. Data collection began with a questionnaire as an initial step, followed by in-depth interviews with selected informants for deeper analysis. Data analysis also includes reliability and validity testing of the questionnaire instruments. The findings indicate that accounting information at the Health Department of Sibolga City has been used in decision-making processes. However, challenges remain in budget planning, particularly with revenue target indicatorsand in performance evaluation concerning revenue realization. These challenges stem from limitations in human resources, such as lack of training and qualifications, and organizational culture factors that hinder optimal utilization of accounting information. In conclusion, while accounting information is being utilized, improving the quality of decision-making requires addressing human resource and organizational culture aspects to ensure accounting information is fully optimized.